Macroeconomic and distributional effects of devaluation in a dollarized economx: A CGE analysis for Bolivia - Rainer Schweickert; Rainer Thiele; Manfred Wiebelt (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
In this paper, a real-financial CGE model is employed for Bolivia to simulate the macroeconomic and distributional effects of exchange rate policy in a highly dollarized economy. Overall, dollarization appears to matter more through real than through financial-sector effects. The main macroeconomic result of the simulations is that the potential of nominal devaluation to smooth the adjustment path after a negative shock primarily depends on the absence of wage indexation. Only if nominal wages are constant in the short run, devaluation reduces unemployment and cushions the reduction of real GDP induced by the shock. Financial de-dollarization tends to be contractionary in Bolivia but different degrees of financial dollarization hardly change the real sector effects. As concerns distributional effects, nominal devaluation in no circumstance reduces the poverty effect of the external shock. Even the significant short-run macroeconomic expansion that occurs without wage indexation does not translate into significant poverty alleviation, given the offsetting effects of devaluation on real factor incomes, real interest incomes, and real transfers received by households.
Keywords: D3; C68; 330; Dollarization; Poverty; Computable General Equilibrium Model; Bolivia